MENINGKATKAN KEAKTIFAN BELAJAR SISWA PADA PEMBELAJARAN PECAHAN DENGAN MENGGUNAKAN MODEL JIGSAW DI KELAS V SDN BENDUNGAN ( IMPROVING STUDENT LEARNING ENGAGEMENT IN FRACTION LEARNING THROUGH THE JIGSAW MODEL IN GRADE V OF SDN BENDUNGAN ELEMENTARY SCHOOL ) - Huda, Syamsul; Dwi Rochmania, Desty (IJPSE Indonesian Journal of Primary Science Education, 2025)
This study aims to enhance student engagement in mathematics learning, particularly in fractions, for fifth-grade students at SDN Bendungan through the cooperative learning model Jigsaw. This classroom action research was conducted in three cycles involving planning, implementation, observation, and reflection stages. The results showed significant improvements in student engagement and learning outcomes. In the first cycle, the average student engagement reached 65%, increasing to 85% in the third cycle. The Jigsaw model effectively enhanced motivation, student involvement in the learning process, and comprehension of fraction material. Therefore, implementing this model is recommended to improve the quality of mathematics learning in elementary schools